THE NUMBERED HEAD TOGETHER LEARNING MODEL ON THE CRITICAL THINKING ABILITY OF IV CLASS SD STUDENTS - Ermawati, Diana; Prameswari, Andin; Nuryanah, Siti; Nashan, Syafiq; Noor, Yuniza Amalia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Mataram, 2024)
The low critical thinking abilities of students are caused by the application of non-innovative learning models. Learning is still teacher-centered so that students cannot develop critical thinking skills to the maximum. The aim of this research is to determine differences in critical thinking abilities of students who are treated using the Numbered Heads Together learning model. This research is quantitative research with the type of experimental research. The research was conducted in class IV of SD N 10 Gondosari. Data analysis was carried out using the t-test (Paired T Test). Based on the results of the T Test (Paired T Test) calculations, the Sig value is obtained. (2-tailed) is 0.000 which means Sig. (2-tailed) < 0.05. From these calculations, the T test results were less than the significance level. It can be concluded that there is a difference in the average test results before and after the Numbered Head Together (NHT) learning model is implemented. There are significant differences in critical thinking abilities between students taught using the Numbered Heads Together learning model.